Human interface and the management of information. interacting with information symposium on human interface 2011, held as part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, proceedings. Part I - HCI 2011 Orlando, F.L.) (2011; Smith, Michael J.; Salvendy, Gavriel; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This two-volume set LNCS 6771 and 6772 constitutes the refereed proceedings of the Symposium on Human Interface 2011, held in Orlando, FL, USA in July 2011 in the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011 with 10 other thematically similar conferences. The 137 revised papers presented in the two volumes were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the thematic area of human interface and the management of information. The 75 papers of this first volume address the following major topics: design and development methods and tools; information and user interfaces design; visualisation techniques and applications; security and privacy; touch and gesture interfaces; adaption and personalisation; and measuring and recognising human behavior.
Electronic reproduction.
Keywords: Human-computer interaction -- Congresses; User interfaces (Computer systems) -- Congresses; Electronic books